Ba9Lu2Si6O24:Ce3+: An Efficient Green Phosphor with High Thermal and Radiation Stability for Solid‐State Lighting. Issue 8 (25th March 2015) - Liu, Yongfu; Zhang, Jianxin; Zhang, Changhua; Xu, Jingtao; Liu, Guoqiang; Jiang, Jun; Jiang, Haochuan
<x xml:space="preserve">Abstract</x> Among the inorganic phosphors used in advanced solid‐state lighting technologies, nitridosilicates have drawn significant attention because of their superior photoluminescence properties with high efficiency and high thermal stabilities. However, the synthesis of nitride phosphors usually requires strict processing conditions and a long processing time, leading to very high manufacturing costs. Herein, a novel orthosilicate green phosphor, Ba9Lu2Si6O24:Ce3+, is synthesized via a simple solid‐state reaction. The photoluminescence characterization identifies a main peak at 400 nm in the excitation spectrum, making it viable for near‐UV LED excitation. This phosphor exhibits a broad emission band with a width of nearly 120 nm, peaking at 490 nm. By optimizing the Ce3+ concentration, an internal quantum efficiency (QE) as high as 82% can be achieved, which is equivalent to that of most nitride phosphors. Furthermore, nearly 94% of the room‐temperature internal QE is still maintained at 160 °C, which is superior to that of most nitride phosphors. The excellent thermal stability and luminescent properties show this compound to be a promising candidate as a green phosphor for near‐UV‐based white LEDs.